Retinaculum Grafts in Scapholunate Ligament Reconstruction: A Systematic Review - Estermann, Lea; Yong, Melodi; York, Blair S.; Tham, Christopher Y.; Onggo, James; Tham, Stephen K. (Journal of Wrist Surgery, 2024)
Background Several surgical techniques for the treatment of the irreparable chronic scapholunate (SL) ligament disruption, without arthritis, have been described using tendon grafts. An alternative technique is the use of retinaculum grafts. A systematic review of the biomechanical and histological properties of the bone–retinaculum–bone (BRB) graft and the clinical results of its use in SL ligament reconstruction was performed.Materials and Methods After abstract screening of 353 articles, a total of eight studies (five laboratory and three clinical) were included.Results Five cadaveric studies showed a lower load to failure and lower stiffness of the BRB compared with the scapholunate interosseous ligament. In patients with dynamic SL instability, treatment with BRB graft resulted in pain relief and an improvement in grip strength but with a reduced range of motion. Radiologically, no SL widening was found 18 months after surgery but with a slight increase after 12 years. The three clinical studies in this review have a level of evidence of 4. There were no studies on graft incorporation and remodeling.Conclusion There is insufficient clinical, histological, and biomechanical data available on the use of BRB grafts for SL ligament reconstruction.
Keywords: scapholunate; ligament; wrist; carpal; instability